MENINGKATKAN HASIL BELAJAR BAHASA INGGRIS DENGANMENGGUNAKAN MODEL PEMBELAJARAN COOPERATIVE TIPE STUDENT TEAMS ACHIEVEMENTDIVISIONS (STAD) PADA MATERI TIMETABLE KELAS VIII SMP NEGERI 9 SOLOK SELATAN - S, Heriansyah. (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
The background of the research is the result of low student learning English , learning outcomes of students do not reach the KKM, this is caused by the learning model used is not in accordance with the material in the teaching and learning process that it makes them unintersted with the materials given , the ability of the students to answer the questions of items is still low, and we still find many students afraid and ashamed to ask some questions about the unknown materials given in the teaching and learning process. Some students often disturb other students and play when the materials are being given by the teacher. The purpose of research conducted to improve student learning outcomes of English using Cooperative Learning Model Type Student Teams Achievement Devisions (STAD). This type of research is the Classroom Action Research ( PTK ). The Subjects were VIII grade students of SMP Negeri 9 South Solok in the second semester of the school year 2019/2020. This research resulted in quantitative data in the form of data obtained from the results of tests conducted at each meeting in each cycle, and qualitatif data obtained from the observation sheet of students. Having conducted research for two cycles, each cycle two meetings, it was through the use of Cooperative Learning Model of Student Teams Achievement Divisions (STAD) Type, researchers succeeded in improving student learning outcomes characterized by an increase in classical learning completeness students. In the first cycle obtained classical learning completeness student by 68 %, then increased in the second cycle to 90%, while improving student learning outcomes from the first cycle to the second cycle by 22%. It can be concluded that the PTK is successfully improving student learning outcomes English Subtitles Time Table.